CO2 measurements during the 2021-2022 Saildrone 1079 mission (Eastern Tropical Atlantic area) - Björn Fiedler; Cathy Wimart-Rousseau; Romain Cancouet; Hervé Claustre; Laurent Coppola; Letícia Cotrim da Cunha; Marine Fourrier; Fabrice Hernandez; Melf Paulsen (PANGAEA, 2023)
In the framework of the EuroSea project (Task 7.3), a demonstration mission in the Tropical Atlantic has been conducted to enhance and optimize the network design of the Tropical Atlantic Observing System (TAOS) following an integrative multi-platform approach. One Gen6 Saildrone Explorer USV equipped with a CTD, wind, and carbon measurements systems sailed to the Cape Verde region where it acquired data between September 2021 and February 2023. Objectives for this mission include developing an integrated multi-platform approach to improving carbon monitoring, data quality, and regional upscaling from moored instrumentation, biogeochemical Argo floats, autonomous surface observation, and remote sensing products. The ASVCO2 system (pCO2 sensor type) on the SailDrone is equipped with on-board reference gas containers to calibrate itself before and after each measurement, and readings of zero gas and reference gas values (that span the ocean pCO2 values of the location where the system is deployed) are made immediately before the calibration.